2015
DOI: 10.1021/acsnano.5b04261
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Conjugated Gold Nanoprobe: Intrinsic Nanozyme-Linked Immunsorbant Assay of Integrin Expression Level on Cell Membrane

Abstract: Precisely quantifying the membrane protein expression level on cell surfaces is of vital importance for early cancer diagnosis and efficient treatment. We demonstrate that gold nanoparticle bioconjugated by a rationally designed peptide as nanoprobe possesses selective labeling and accurate quantification capacity of integrin GPIIb/IIIa on the human erythroleukemia cell line. Through selective recognition and marking of integrin, two-photon photoluminescence of the nanoprobe is exploited for direct observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 42 publications
2
65
0
Order By: Relevance
“…For a typical oxidation reaction, the time-dependent absorbance of the solution of 0.1 mM TMB and 0. (10,25,50,75, 100 mg mL À1 ) were used to show the chromogenic reactions implying oxidaselike activity. The steady-state kinetic assays of 50 mg mL À1 Ru NPs with TMB (0.05, 0.1, 0.2, 0.5 mM) as the substrate were performed at room temperature.…”
Section: Tmb Oxidation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For a typical oxidation reaction, the time-dependent absorbance of the solution of 0.1 mM TMB and 0. (10,25,50,75, 100 mg mL À1 ) were used to show the chromogenic reactions implying oxidaselike activity. The steady-state kinetic assays of 50 mg mL À1 Ru NPs with TMB (0.05, 0.1, 0.2, 0.5 mM) as the substrate were performed at room temperature.…”
Section: Tmb Oxidation Studiesmentioning
confidence: 99%
“…[6][7][8] As a promising candidate for articial enzymes, nanomaterials with intrinsic enzyme-like activity known as nanozymes ignite intensive research interest due to their ability to replace specic enzymes in enzyme-based applications. [9][10][11][12][13] The design and development of novel nanostructured materials mimicking the catalytic role of natural enzymes has emerged as a promising eld for both fundamental and applied research. Since the discovery by Yan and coworkers that Fe 3 O 4 nanoparticles possess intrinsic peroxidase-like activity and show potential to replace natural peroxidase in bioassays, 14 substantial research is directed toward the development of nanomaterial catalysts that mimic functions of peroxidase, oxidase or other natural enzymes with the advantages of low cost, controlled synthesis, tunable catalytic activities, and high stability even under severe reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, gold nanoparticles (Au NPs) have been widely applied in biomedical fields such as drug delivery, phototherapy, diagnosis, and biosensing due to their unique properties. Designing efficient nanocarriers for detection, imaging, and targeted therapeutic applications of Au NPs demand well understanding of the endocytosis, exocytosis, and their specific mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In another example, Gao et al reported AuNPs conjugated by a rationally designed peptide (H 2 N-CCYKKKKQAGDV-COOH) as nanoprobe for targeting integrin GPIIb/IIIa. 89 In the presence of H 2 O 2 , peptide-AuNPs acted as robust catalyst to catalyze the oxidation of 3,3',5,5'-tetramethylbenzidine (TMB) to ox-TMB (Fig. 9a).…”
Section: Biocatalysismentioning
confidence: 99%
“…c. Schematic illustration of peptide-AuNP-mediated cancer cell immunoassay. d. Linear regression associates HEL cell number with Au concentration (red curve) and catalytic colorimetric variation (blue curve) 89. Reproduced from Gao et al © 2015 American Chemical Society.…”
mentioning
confidence: 99%